Textual Coherence in the Poem Masabi Jalil by Abu Firas Al-Hamdani: A Textual Linguistic Study in Light of Text Grammar Theory - Al-Qudah, Mohammad Ahmad; Al-Abani, Salmeen Mohammad (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to uncover instances of textual coherence in a poem from the Romances of Abu Firas al-Hamdani, as well as the textual criteria that have given the poem textual coherence and harmony. It also aims to explore the extent of presence of each tool among those textual criteria, its role, and its impact on the text, all in the light of text linguistics theory and discourse analysis. It also aims to explore the extent of presence of each tool among those textual criteria, its role, and its impact on the text, all in the light of text linguistics theory and discourse analysis. Method: This study followed a descriptive and analytical textual approach, which proceeds in light of research methodologies that facilitate a thorough understanding and analysis of the text. This method aims to identify the textual criteria within it in order to reach positions of its strength, coherence, and consistency. Results: The coherence and consistency of texts have become an important matter that must be present within every text. Understanding the syntactic and semantic relationships between the words of the sentence itself, and between the sentences within the text, allows the reader or recipient to grasp some of the initial semantic threads that connect the parts of the text to each other, as well as connecting them to the reality of the text and the circumstances accompanying its production. Conclusion: The poem formed a cohesive textual structure consisting of forty verses, in which a network of syntactic and lexical relationships intertwined to bring it to the level of creativity and highlight its aesthetics.